HOW IS PARTICIPATORY PLANNING PERCEIVED WITHIN REPRESENTATIVE SYSTEM?: A SWEDISH CASE OF ULLERÅKER REGION - Pınar Akarçay (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The participatory planning approach that emerged in urban planning in recent years is based on collaborative, communicative, and deliberative planning processes that cover the differences. The main purpose of participatory planning is to include the perspective of actors (political representatives, planners, citizens) in planning processes by developing horizontal planning tools and processes among actors. However, the decision-making system in Sweden is built on representative democracy based on top-down policy-making processes and vertical relations. Therefore, the simultaneous coexistence of representative top-down policy-making processes and multi-faceted participatory arrangements make Sweden an interesting example and suggests that some dilemmas and tensions may arise in practice. At this point, in a political system with strong representative democracy like Sweden, it provides important data on how actors perceive participatory planning and how participatory planning is implemented. In this context, this research discussed how participatory planning is perceived in urban planning in the logic of representative democracy in Sweden. Ulleråker region of Uppsala, in particular, was chosen to carry out the field research, and thus, interviews on the subject were conducted in this region with the main actors of decision-making processes in urban planning such as political representatives, public officials/planners, and citizens.